A new benzophenone C-glucoside and other constituents of pseuduvaria fragrans and their α-glucosidase inhibitory activity - Wongvarit Panidthananon (2018)
© 2018 by the authors. Phytochemical investigations of the leaves and stems of Pseuduvaria fragrans led to the isolation of a new benzophenone C-glucoside named pseuduvarioside (1), together with six known compounds including (−)-guaiol (2), (+)-isocorydine (3), cyathocaline (4), isoursoline (5), N-trans-coumaroyltyramine (6), and N-trans-feruloyltyramine (7). Their structures were characterized by NMR spectroscopy and mass spectrometry. All of the isolates were evaluated for inhibitory activity against the enzyme α-glucosidase. N-trans-coumaroyltyramine and N-trans-feruloyltyramine showed higher activity than the drug acarbose. Kinetic studies revealed that both tyramine-derived amides were uncompetitive inhibitors of the enzyme.